An atom- and pot-economical consecutive multi-step reaction approach to polycyclic aromatic hydrocarbons (PAHs). Issue 11 (24th January 2017) - Raji Reddy, Chada; Dilipkumar, Uredi; Shravya, Ravula
Abstract : A novel [4+2]-benzannulation approach to substituted polycyclic aromatic hydrocarbons has been developed under atom-economical, mild and metal-free reaction conditions. Abstract : A novel one-pot benzannulation reaction has been developed for the synthesis of substituted polycyclic aromatic hydrocarbons (PAHs) from the direct coupling of propargylic aldehydes/alcohols with 1, 1-diarylethanol through an atom-economical uninterrupted three/four-step reaction sequence under mild and metal-free reaction conditions. The strategy involves an acid-catalyzed dehydration and carbon–carbon bond formation followed by DBU-promoted cycloisomerization. Naphthalene and phenanthrene were obtained via mono-benzannulation, and chrysene, picene and benzopicene were obtained involving consecutive di-benzannulation reactions in good yields starting from easily accessible starting materials.